Krisis Kemanusiaan dan Upaya Thailand Mengatasi Gelombang Pengungsi Rohingya - Ludfiani, Anifa; Hara, Abubakar Eby; Sunarko, Bagus Sigit (University of Jember, 2017)
Abstract Myanmar is a country which is highly vulnerable to ethnic conflict. It is a risk for Myanmar as a multiethnic country which has 135 ethnics. In 2012 and 2015, the worst intensity of the conflict was in Rakhine region. There was conflict between Rakhine Buddhist ethnic and Rohingya minority ethnic. This conflict caused 140,000 Rohingya people had to flee in 2012, and the number continued to increase as the continuation of the uprising, slaughter and expulsion carried out by Rakhine Buddhists ethnic. As a result, in 2012 to 2015, there was a wave of Rohingya refugees from Myanmar towards neighboring countries. The wave itself was out of control. One of the destination countries of Rohingya refugees was Thailand. This caused Thailand has the responsibility to provide humanitarian assistance in accordance with the principle of